A MENSURAÇÃO DA EFETIVIDADE DOS DIREITOS HUMANOS FUNDAMENTAIS: REFLEXÕES E ANÁLISES SOBRE AS COTAS UNIVERSITÁRIAS E O SANEAMENTO BÁSICO - FÁBIO ZANCHETTIN (2024)
The central theme of this work is the analysis of mechanisms capable of measuring the effectiveness of human rights materialized through concrete and measurable actions. The justification for the study is related to the central roles played by measurement and evaluation in contemporary society. Using a deductive approach methodology, the study, predominantly descriptive and exploratory, to be conducted with support from bibliographic and historical research, aims primarily to investigate mechanisms capable of measuring the effectiveness of human rights; and, as specific objectives, discuss the origin of human rights, analyze the evolution of these rights, study the theory of dynamogenesis of values, explore how the Sustainable Development Goals (SDGs) relate to the utopian aspiration of human rights, and address the evolution of philosophical thought regarding human rights, racism, and tolerance, in order to subsequently contextualize the Quota Law as an affirmative action, exposing some of its foundations that led to its promulgation at the time, as well as its recent update. In order to propose mechanisms capable of measuring the effectiveness of human rights, the inductive procedure method with a quantitative bias will be adopted, utilizing data from the Brazilian Institute of Geography and Statistics (IBGE), the National High School Exam (ENEM), the Program for International Student Assessment (PISA), and the United Nations Statistics Division (UNSD).